2016
DOI: 10.20527/k.v4i2.263
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Bioaktivator Em4 Dan Promi Dalam Pembuatan Pupuk Cair Organik Dari Sampah Organik Rumah Tangga

Abstract: Abstrak-Pemanfaatan  sampah organik rumah tangga tiap tahun meningkat karena berbagai permasalahan yang akan timbul seperti polusi udara, dapat menimbulkan dampak penyakit dan bahaya banjir. Sampah yang dapat dimanfaatkan adalah sampah organik berupa sisa sayuran, sisa buah-buahan, sisa daun kering, dan ranting pohon. Sampah organik rumah tangga ini  paling banyak digunakan dalam kehidupan sehari-hari karena kebutuhan akan makanan sehingga kuantitasnya semakin banyak dihasilkan  dan akan menumpuk karena tanah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…Furthermore, Nurhasanah (2020) also suggested that Effective Microorganisms contains microorganisms that are beneficial for plants because they can boost growth and increase the population of microorganisms. Additionally, Effective Microorganisms have the properties to speed up the decomposition of wastes and functions as a bio activator against liquid fertilizer production (Marlinda, 2015). Adding coconut water and 5ml Effective Microorganisms was sufficient to increase the number of leaves (resulting in the same results as adding 15 ml Effective Microorganisms).…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, Nurhasanah (2020) also suggested that Effective Microorganisms contains microorganisms that are beneficial for plants because they can boost growth and increase the population of microorganisms. Additionally, Effective Microorganisms have the properties to speed up the decomposition of wastes and functions as a bio activator against liquid fertilizer production (Marlinda, 2015). Adding coconut water and 5ml Effective Microorganisms was sufficient to increase the number of leaves (resulting in the same results as adding 15 ml Effective Microorganisms).…”
Section: Resultsmentioning
confidence: 94%
“…According to Sundari et al (2012), the use of EM4 can accelerate the fermentation process for the manufacture of liquid fertilizer. In addition, EM4 will accelerate the fermentation of organic matter so that the nutrients contained will be absorbed and available to plants (Marlinda, 2015). Previous study stated that the more volume of EM4 added, the faster the fermentation process and the reshuffling of raw materials into elements that are easily absorbed by plants in the form of N, P, and K will be completed.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-anaerobic fermentation requires optimal conditions, namely low pH (3-4), high salt and sugar content, moderate water content of 30-40%, and ambient temperature around 40-50 C (Marlinda, 2015;Nur et al, 2016). Temperature is very influential on the fermentation process because it is related to the types of microorganisms involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations